Instructional Experiences of Fifth Grade Students with Keyboarding Instruction - Bullock, Thomas (Valdosta State University, 2005)
The purpose of my study was to investigate the instructional experiences of fifth grade students in regard to keyboarding instruction and to examine student handwriting speed in relation to keyboarding speed. Forty-three fifth graders in two classes participated in this study. The intervention consisted of 19 days of keyboarding instruction via the Type to Learn software program. Data collection included pre and post measurements of handwriting and keyboarding speed, observation checklists, student perception surveys, and student interviews. Results from the study indicated that students, even after 19 days of keyboarding instruction, possess faster handwriting speeds than keyboarding speeds. Results also indicated limited improvement in keyboarding speed after keyboarding instruction, but indicated positive student experience with keyboarding instruction and high levels of motivation toward continuing instruction. Negligible differences were noted between students who used keyboard masks and those who did not. Findings suggest that a longer instruction period is necessary to produce keyboarding speeds that match handwriting speeds and that keyboarding instruction can be a positive experience for elementary students when planned in a developmentally appropriate manner.
Keywords: keyboarding instruction; handwriting speed; keyboarding speed; Type to Learn; Educational technology; Teaching--Aids and devices; Computer-assisted instruction